BIM for building refurbishment and maintenance: current status and research directions. Issue 3 (13th July 2015) - Ilter, Deniz; Ergen, Esin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a strategic overview of the current literature on "Building information modelling (BIM) for Building Refurbishment and Maintenance" to unfold the factors behind the relative underdeveloped state of the field and to contribute to the development of a more cumulative knowledge base by presenting the current status and suggesting future directions for research. Design/methodology/approach – A systematic review of the literature has been undertaken by classifying and mapping the literature, identifying the input-output relations, exhibiting the areas focused on by researchers as well as neglected ones and by indicating the trends in research through the years. Both qualitative and quantitative analysis is used in the study to better interpret the existing studies in a holistic perspective. Findings – Although the need for BIM in facility management (FM) has been acknowledged by researchers and practitioners, the results highlight that studies related to BIM applications in maintenance and especially refurbishment are relatively recent. However, the trend in published articles shows that the interest is continuously growing. Existing research in this field can be clustered in the following subtopics: (1) building survey and as-built BIM, (2) modelling and managing energy, (3) design assessment, (4) access to and integration of maintenance information and knowledge, and (5) information exchange and interoperability. Originality/value – The paper identifies the gaps in the research domain that hinders a widespread adoption of BIM in refurbishment and maintenance stages and introduces roadmaps to surmount the challenges identified in each specific subtopic of the field.